2008
DOI: 10.1002/cphc.200800328
|View full text |Cite
|
Sign up to set email alerts
|

Europium‐Doped Mesoporous Titania Thin Films: Rare‐Earth Locations and Emission Fluctuations under Illumination

Abstract: Herein, Eu(III)-doped 3D mesoscopically ordered arrays of mesoporous and nanocrystalline titania are prepared and studied. The rare-earth-doped titania thin films-synthesized via evaporation-induced self-assembly (EISA)-are characterized by using environmental ellipsoporosimetry, electronic microscopy (i.e. high-resolution scanning electron microscopy, HR-SEM, and transmission electron microscopy, HR-TEM), X-ray diffraction, and luminescence spectroscopy. Structural characterizations show that high europium-io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…In these films, the ratio is about 6-8 (see figure 8). This is similar to the reported values (6)(7)(8)(9)(10)(11)(12) [39], indicating that Eu 3+ ions are located at a low-symmetry site lacking the inversion center, whether they are in the well-crystallized phase, in amorphous phase or in a site characteristic of small nanoparticles. The low site symmetry is confirmed also by the three peaks in the region of the 5 D 0 → 7 F 1 transition, indicating that the symmetry around the Eu 3+ ions is lower than, e.g.…”
Section: Euti@zno Thin Filmssupporting
confidence: 90%
“…In these films, the ratio is about 6-8 (see figure 8). This is similar to the reported values (6)(7)(8)(9)(10)(11)(12) [39], indicating that Eu 3+ ions are located at a low-symmetry site lacking the inversion center, whether they are in the well-crystallized phase, in amorphous phase or in a site characteristic of small nanoparticles. The low site symmetry is confirmed also by the three peaks in the region of the 5 D 0 → 7 F 1 transition, indicating that the symmetry around the Eu 3+ ions is lower than, e.g.…”
Section: Euti@zno Thin Filmssupporting
confidence: 90%
“…Very similarly shaped PL spectra have also been observed before and been described as typical for a Eu 3+ doped disordered system. 10 Leroy et al 13 observed very similar spectra for PL from Eu 3+ doped mesoporous titania with the same gradual spectrum change accompanying the change from anatase to amorphous phase. Comparing the AFM images, XRD data, and PL spectra, there is a clear correlation between the amount of crystallites, the XRD peak intensities, and ratio between the two overlapping PL spectra.…”
Section: Discussionmentioning
confidence: 55%
“…The PL from the inlet strip of 10Eu also has a shape that is consistent with Eu 3+ doped anatase. 13,18 The PL from 80Eu has smeared out peaks which one can imagine arise from the continuous slight variation in the coordination environment for a cation in an amorphous oxide where the bond angles are varying. Very similarly shaped PL spectra have also been observed before and been described as typical for a Eu 3+ doped disordered system.…”
Section: Discussionmentioning
confidence: 99%
“…Such systems developed by different groups [9][10][11][12][13][14] are very attractive materials for multiple domains of applications. Recently, we evidenced the locations adopted by the rare-earth ion within titania mesoporous thin films [15]. We have shown that rare-earth ions are well dispersed into two distinct phases of the titania pore wall structure framework.…”
Section: Introductionmentioning
confidence: 99%